COMPARATIVE ANALYSIS OF LEGISLATION ON CITIZEN PARTICIPATION IN PUBLIC ORDER PROTECTION AND PUBLIC SAFETY: THE EXPERIENCE OF KAZAKHSTAN, RUSSIA, BELARUS, AND TAJIKISTAN (Scientific Conference on Multidisciplinary Studies, 2025)
This study explores the legislative frameworks regulating citizen participation in maintaining public order and safety in Kazakhstan, Russia, Belarus, and Tajikistan. Drawing on the Soviet tradition of voluntary people’s patrols ("druzhinas"), these countries have developed unique yet interconnected approaches to address modern security challenges, combining state control with local initiative. The research analyzes key laws – Kazakhstan’s Law No. 590 (2004), Russia’s Federal Law No. 44-FZ (2014), Belarus’s Law No. 214-Z (2003), and Tajikistan’s Law No. 1969 (2023) – focusing on their core principles, participants’ rights and duties, as well as the strengths, weaknesses, similarities, and differences of these systems. Based on legal documents, government reports, and academic literature, it identifies best practices, including Russia’s adaptable regional models, Kazakhstan’s prevention-focused strategies, Belarus’s structured state coordination, and Tajikistan’s community councils. These findings offer practical recommendations for mutual learning and enhanced cooperation within the Eurasian Economic Union (EAES) and Collective Security Treaty Organization (CSTO).